2021
DOI: 10.1177/0706743721996114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of a Critical Time Intervention Adaptation on Health Care Utilization among Homeless Adults with Mental Health Needs in a Large Urban Center

Abstract: Objective: This study evaluated the impact of a critical time intervention (CTI) adaptation on health care utilization outcomes among adults experiencing homelessness and mental health needs in a large urban center. Methods: Provincial population-based administrative data from Ontario, Canada, were used in a pre–post design for a cohort of 197 individuals who received the intervention between January 2013 and May 2014 and were matched to a cohort of adults experiencing homelessness who did not receive the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The study found four domains of the WHOQOL that were consistent with previous research on the WHOQOL-BREF [ 77 , 78 , 79 ]. Although some earlier research indicated that, in some cases, the factor extraction of the WHOQOL-BREF could be a one-factor solution [ 80 , 81 ], the four-factor solution was deemed necessary for a better model fit, as the former has disadvantages in terms of inter-item correlations [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found four domains of the WHOQOL that were consistent with previous research on the WHOQOL-BREF [ 77 , 78 , 79 ]. Although some earlier research indicated that, in some cases, the factor extraction of the WHOQOL-BREF could be a one-factor solution [ 80 , 81 ], the four-factor solution was deemed necessary for a better model fit, as the former has disadvantages in terms of inter-item correlations [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, CATCH aims to support individuals in the critical period following hospital discharge by providing coordinated physical and mental medical care, peer support and intensive case management over a period of 3–6 months. Previous program evaluations have associated CATCH with improvements in mental health and substance use symptoms and health status ( 11 ), fewer and shorter hospitalizations, more frequent outpatient psychiatrist visits ( 46 ), and continuity of care ( 45 ).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The Coordinated Access to Care for the Homeless (CATCH) program is a multidisciplinary brief case management program for individuals experiencing homelessness and mental illness being discharged from hospital in Toronto, Canada. Informed by the Critical Time Intervention model, the program was launched in 2010 and has been described extensively elsewhere (11,12,(45)(46)(47)(48). Briefly, CATCH aims to support individuals in the critical period following hospital discharge by providing coordinated physical and mental medical care, peer support and intensive case management over a period of 3-6 months.…”
Section: Program Descriptionmentioning
confidence: 99%
See 2 more Smart Citations